Acceptability and feasibility of using vaginal menstrual cups among schoolgirls in rural Nepal: a qualitative pilot study - Diksha Pokhrel; Sabina Bhattarai; Malin Emgård; Michael von Schickfus; Birger C. Forsberg; Olivia Biermann (BMC, 2021)
Abstract Introduction Menstrual hygiene management can be challenging in low-income settings and among school-aged girls due to traditional beliefs, lack of knowledge and information on best hygienic practices, and limited access to appropriate and affordable menstrual hygiene products. An alternative method for menstrual hygiene management, instead of sanitary pads or tampons, is the vaginal menstrual cup. As evidence on the use of menstrual cups is relatively limited, this study aimed to explore the acceptability and feasibility of using vaginal menstrual cups among school-aged girls in Thokarpa, Sindupalchowk, Nepal. Methods This is an exploratory study based on four focus group discussions with a purposive sample of 28 schoolgirls between 13 and 19 years of age who were provided with vaginal menstrual cups in Thokarpa, Sindupalchowk, Nepal. The data were collected between February and March 2019, i.e. approximately three months after the distribution of the menstrual cup. Participants were included in the study if they had started their menstruation and never given birth. Conventional content analysis was applied. Results Most participants perceived the menstrual cup positively. Not missing a single class in school due to problems related to menstrual hygiene management was described as a major benefit. The participants found using the menstrual cup easy and convenient, and described economic and environmental advantages of using it. Cleaning the menstrual cup did not cause any problems, according to the participants. Discomforts mentioned by the participants were: pain when inserting the menstrual cup, feeling the menstrual cup sticking out of the vagina, feeling a constant urge to urinate and leakage. Concerns were related to the size, shape and texture of the menstrual cup, and that it may "get stuck" in the vagina, while relatives were said to be concerned about the use of the menstrual cup leading to reduced fertility or losing virginity. Conclusion The use of vaginal menstrual cups for menstrual hygiene management among schoolgirls in Thokarpa, Sindupalchowk, Nepal, appears feasible and acceptable, as it involves practical, economic and environmental advantages. However, the scale-up of menstrual cups will require resolving described concerns and discomforts and fostering peer and family support.